The Role of Scouting Extracurricular in Developing the Attitude of Students’ - Muhamad Ali Gunawan; Rambat Nur Sasongko; Muhammad Kristiawan; Sudarwan Danim (Budapest International Research and Critics University, 2022)
The background of this research is that the role of scouting extracurricular at SMAN Surulangun, Musi Rawas Utara district is unknown in developing student attitudes. This research was conducted to know the role of extracurricular scouting at SMAN Surulangun, Musi Rawas Utara district in developing the attitudes of students in grades X, XI, and XII. The research method used is a survey method with exploratory purposes. The data collection technique used is a questionnaire with data analysis techniques using descriptive statistics. The subjects in this study were 37 students at SMAN Surulangun. The results showed that the role of extracurricular scouting in developing the attitudes of SMAN Surulangun students, as many as 17 respondents (46%) were included in the good category and 20 respondents (54%) were included in the very good category. This means that scouting extracurricular activities affect the positive character of students such as the character of discipline, responsibility, independence, and honesty, scouting extracurricular activities has an important role in growing these characters because scouting extracurricular activities are considered interesting activities for students so that through scouting extracurricular activities students can be easily trained and accustomed to discipline, responsibility, independence, and honesty by complying with the established rules.